In vitro Natural Killer Cell Immunotherapy for Medulloblastoma - Fernandez, Lucia; Portugal, Raquel; Valentin, Jaime; Martin, Roberto; Maxwell, Hannah; González-Vicent, Marta; Díaz, Miguel Ángel; Pérez-Martínez, Antonio (Frontiers in Oncology, 2013)
How the immune system attacks medulloblastoma (MB) tumours effectively is unclear, although natural killer (NK) cells play an important role in immune defence against tumour cells. Interactions between receptors on NK cells and ligands expressed by tumour cells are critical for tumour control by immunotherapy. In this study, we analysed tumour samples from 54 MB patients for expression of major histocompatibility complex class I-related chains A (MICA) and UL16 binding protein (ULPB-2), which are ligands for the NK group 2 member D activatory receptor (NKG2D). The percentage of MICA and ULBP-2 positive cells was higher than 25% in 68% and 6% of MB patients, respectively. A moderate-high intensity of MICA cytoplasmic staining was observed in 46% MB patients and weak ULBP-2 staining was observed in 8% MB patients. No correlation between MICA/ULBP-2 expression and patient outcome was found. We observed that HTB-186, a medulloblastoma cell line, was moderately resistant to NK cell cytotoxicity in vitro. Blocking MICA/ULBP-2 on HTB-186, and NKG2D receptor on NK cells increased resistance to NK cell lysis in vitro. However, HLA class I blocking on HTB-186 and overnight incubation with IL-15 stimulated NK cells efficiently to kill tumour cells in vitro. We conclude that although NKG2D/MICA-ULBP-2 interactions have a role in NK cell cytotoxicity against MB, high expression of HLA class I can protect MB from NK cell cytotoxicity. Even so, our in vitro data indicate that if NK cells are appropriately stimulated, they may have the potential to target MB in vivo.